The Utilization of Cytologic Fine-Needle Aspirates of Lung Cancer for Molecular Diagnostic Testing - Michael H. Roh (Korean Society of Pathologists & the Korean Society for Cytopathology, 2015)
In this era of precision medicine, our understanding and knowledge of the molecular landscape associated with lung cancer pathogenesis continues to evolve. This information is being increasingly exploited to treat advanced stage lung cancer patients with tailored, targeted therapy. During the management of these patients, minimally invasive procedures to obtain samples for tissue diagnoses are desirable. Cytologic fine-needle aspirates are often utilized for this purpose and are important not only for rendering diagnoses to subtype patients' lung cancers, but also for ascertaining molecular diagnostic information for treatment purposes. Thus, cytologic fine-needle aspirates must be utilized and triaged judiciously to achieve both objectives. In this review, strategies in utilizing fine-needle aspirates will be discussed in the context of our current understanding of the clinically actionable molecular aberrations underlying non-small cell lung cancer and the molecular assays applied to these samples in order to obtain treatment-relevant molecular diagnostic information.